(untitled) (Journal of Pedagogical Inventions and Practices, 2022)
This research aims to find outCan digital libraries develop students’ reading skills? This research was deliberately conducted to be able to test whether the theory found was in accordance with the reality in the field. This researchusing the observation approach method. The results showed that there was progress in reading ability in grade 4 students at SDN 90 Sipatana. This means that the digital library is one of the things that really helps students to develop reading skills.